Ekstraksi Senyawa Tanin dari Biji Alpukat (Persea americana mill.) menggunakan Pelarut Air Subkritis - Qifni Yasa, A.S.; Daniyal Agung A.; Karyana Karyana (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Hydrothermal extraction of tannic acid from avocado seed using Subcritical water as a solvent wasevaluated at temperatures of 110oC, 120oC and 130oC, extraction time of 30-150 minutes and performedunder batch condition using Batch reactor, This method is easy to do and Enviromental-friendly. TheAnalytical method that used in this research was Spectrophotometry UV-Vis Method. Folin ciocalteau usedas a reagent that indicate Tannic Acid amount in Avocado seed extract. Under hydrothermal condition,water act as a extremely good solvent despite of its unique characteristics, high ion product and lowdielectric constant, moreover, in these condition, there is possibility for the occurence of tannic acid fromavocado seed. As a result, The total phenolic compound increased significantly from 110oC to 120oC andslowly decreased when temperature rised. Tannic acid is very sensitive to high temperature. The result of thisresearch showed that the optimum extraction temperature was at 120oC with 30 minutes of extraction time.The highest yield of tannic acid could approach 81 mg/kg of sample. Hydrothermal extraction isconsiderable method to isolate tannic acid and phenolic compounds from the waste of biomass.